About various aspects of self-management of the entrepreneurs in the conditions of crises and risks - R. N. Botavina (Путеводитель предпринимателя)
In the article features of entrepreneurship in the modern society are considered. Recommendations about self-management of the entrepreneurs in the conditions of crises and risks - in the presence of a tendency of their growth are made.